Vulnerable Life in Marvell's Mower Poems. Issue 1 (27th March 2019) - Kerr, Jason A.
Abstract : This essay reads Marvell's mower poems and 'The Garden' as case studies in the ethics of vulnerability that collectively work to illuminate a potential for joyful connection—with people, but also with the natural world—in the practice of critique, which otherwise has a melancholic potential for over-identifying with its object. Whereas vulnerability commonly denotes susceptibility to harm, this essay builds on the work of Erinn Gilson to show that vulnerability is ontological, a shared feature of human existence that makes both harm and connection possible. Vulnerability figures in the poems through the relationships they depict: between the mower and himself, Juliana, and the grass. As a counterbalance to the various strategies that they deploy to escape the vulnerability (and potentiality for harm) occasioned by these relationships, the poems also present the possibility of an 'innocent', non-violent relationship of mutual fruitfulness with the grass—a possibility that at least hypothetically extends to relationships with other people. These latter possibilities suggest a form of critique that escapes its melancholic temperament—the presumption that the world portends only harm—and allows even complicity to contain the potential for joyful, mutual, and fruitful connection with others.